2009
DOI: 10.1590/s0074-02762009000200036
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with seropositivity for anti-Toxoplasma gondiiantibodies in pregnant women of Londrina, Paraná, Brazil

Abstract: The aim of this study was to evaluate associations between seropositivity for IgG and IgM anti-Toxoplasma gondii antibodies and socio-economic and environmental variables in pregnant women of Londrina, state of Paraná, Brazil. We interviewed 492 pregnant women, each of whom answered an epidemiological questionnaire, and collected blood samples for measurement of IgG and IgM anti-T. gondii antibodies by chemiluminescence. A confirmatory diagnosis of acute infection was made by an IgG avidity test. Titres of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
30
5
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 19 publications
(23 reference statements)
18
30
5
7
Order By: Relevance
“…However, through multivaried analysis, it was found that there was no association between this factor and infection by T. gondii, agreeing with other studies done in the southern region of Brazil 4,18 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, through multivaried analysis, it was found that there was no association between this factor and infection by T. gondii, agreeing with other studies done in the southern region of Brazil 4,18 .…”
Section: Discussionsupporting
confidence: 89%
“…The low level of instruction of the analyzed patients explains the lack of knowledge about the ways of transmission of toxoplasmosis, in agreement with another study conducted in the same city 4 . This makes it evident that improvements in the quality of education are needed, especially because the level of instruction lowers the exposure to risks, this is down to the adoption of more appropriate measures of hygiene and nutrition by the subjects 18,28 .…”
Section: Discussionmentioning
confidence: 99%
“…The pregnant women resident in rural areas presented a prevalence of 75.68% (28/37) and a greater chance of infection by T. gondii (OR = 2.70) when compared to the others from the urban areas (Table 2) 38 in the city of Londrina, Paraná, where they observed that the prevalence of specific IgG antibodies increased with ages between 31 to 48. In a study performed in Sergipe State with 9,500 pregnant women, a greater prevalence was found of anti-T. gondii antibodies proportionally to the age 1 19 , in the city of Caxias do Sul, Rio Grande do Sul, also reported a significant association between prevalence and the age of women studied (p < 0.001) with greater frequency in the ones between 37 to 49 years old (51.7%).…”
Section: Discussionmentioning
confidence: 96%
“…Regarding the prevalence of IgM antibodies, MITSUKA-BREGANÓ (2009) 41 and LOPES et al (2009) 38 found a lower prevalence in pregnant women in Londrina, Paraná, which was 0.5% and 1.2%, respectively. Similar results were found in pregnant women such as 2.2% 6 in Santo Ângelo and 2.6% 49 in Porto Alegre, both from the Rio Grande do Sul State.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the level of education, income level, the presence of cats at home, and the habit of eating vegetables are factors associated with a higher chance of T. gondii infection 17 . Innes and Dabritz & Conrad used epidemiological surveys to emphasize the importance of the cat in the transmission of toxoplasmosis to intermediary hosts 18,19 .…”
Section: Fonseca Al Et Al -Toxoplasmosis Epidemiologymentioning
confidence: 99%